In the Foot Step of Consolidating Ummah: Highlights from the 7th Indonesian Muslim Congress - Garadian, Endi Aulia (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
Indonesia might be considered as